2007
DOI: 10.1091/mbc.e06-10-0885
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Remodeling of GPI-anchored Proteins Is Required for Their Raft Association

Abstract: Whereas most of the cellular phosphatidylinositol (PI) contain unsaturated fatty chains and are excluded from rafts, GPI-anchored proteins (APs) unusually contain two saturated fatty chains in their PI moiety, and they are typically found within lipid rafts. However, the origin of the saturated chains and whether they are essential for raft association are unclear. Here, we report that GPI-APs, with two saturated fatty chains, are generated from those bearing an unsaturated chain by fatty acid remodeling that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
185
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(200 citation statements)
references
References 44 publications
7
185
0
1
Order By: Relevance
“…Inositol deacylation by PGAP1 is required for the efficient transport of GPI-anchored proteins from the ER to the Golgi, as described in Section D. In yeast, the reaction is also needed for the efficient degradation of misfolded GPIanchored proteins (38). In addition, inositol deacylation is indispensable for the following fatty acid remodeling described in Section C-4 (39). Fatty acid remodeling is not actually performed in human erythrocytes, which express inositol-acylated GPI-anchored proteins.…”
Section: C-2 Inositol Deacylationmentioning
confidence: 99%
See 2 more Smart Citations
“…Inositol deacylation by PGAP1 is required for the efficient transport of GPI-anchored proteins from the ER to the Golgi, as described in Section D. In yeast, the reaction is also needed for the efficient degradation of misfolded GPIanchored proteins (38). In addition, inositol deacylation is indispensable for the following fatty acid remodeling described in Section C-4 (39). Fatty acid remodeling is not actually performed in human erythrocytes, which express inositol-acylated GPI-anchored proteins.…”
Section: C-2 Inositol Deacylationmentioning
confidence: 99%
“…Mammalian PGAP3 (yeast Per1p) is a multiple membrane-spanning protein required for GPI phospholipase A 2 activity during fatty acid remodeling (39,53). Recently, it was reported that PGAP3 together with alkaline ceramidase form a superfamily of putative transmembrane hydrolases named CREST (54).…”
Section: C-4 Fatty Acid Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The ceramide structure of each glycosphingolipid is highly variable (7), whereas GPI-anchored proteins contain C18 and/or C16 fatty acid chains. In particular, the C18:0 fatty acid chain at the sn-2 position of GPIanchored proteins is critical for their association with membrane microdomains (8), while the presence of a 24:0 or C24:1 fatty acid chain in glycosphingolipids has been demonstrated to be necessary for their functional connection with Src family members in membrane microdomains (6,9). In contrast, GPI-anchored receptor clusters transiently recruit Src family kinases, leading to their temporary immobilization and consequent activation (10,11).…”
Section: 緒 言mentioning
confidence: 99%
“…Furthermore, recent data strongly suggest they could also play a determinant role in mammalian cells in the distribution of GPI proteins between subset of microdomains [72]. Fatty acid remodeling of the GPI anchors, required for their association with membrane ordered domains [45,65], could be part of the process leading to the synthesis of these specific anchors. In accordance with this view, the differen- In this experiment, the amount of BIAP incorporated in the bilayer was much lower than in Fig.…”
Section: Predictable Consequences For Biomembranesmentioning
confidence: 99%